Metode Hermeneutik dalam Pendidikan - Ardi Widodo, Sembodo (Unisia, 2012)
Hermeneutics is an art of interpretation or a philosophical study of understanding. It has wider range of understanding; not only canonical texts, but also all texts, from teaching manuals to literary classics. Human acts and products, such as the act of teaching and the institution of school or university are interpreted. Here, we can see that the formulation of vision, mission, and the goal of any school and university is a result of interpretation or dialogue. Not only in this educational aspect hermeneutics plays its role, but also in teaching-learning aspect. According to hermeneutics, teaching is an art, not a science or technology. Teaching-learning process is like a dialogue or game in which participants are carried by something larger than themselves toward an insight they have not anticipated. Dialogue presupposes a subject and a desire to understand it. Openness on both sides is essential. No one must come with his mind made up. In a give and take, each participant arrives at a new understanding. Finally, genuine dialogue makes fusion of each participant’s mental horizon. Keywords: hermeneutics, interpretation, philosophy, understanding, education.